2020
DOI: 10.1002/cpt.1827
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Placental Disposition of Infliximab and Etanercept in Women With Autoimmune Diseases and in the Ex Vivo Perfused Placenta

Abstract: Tumor necrosis factor (TNF) inhibitors are increasingly applied during pregnancy without clear knowledge of the impact on placenta and fetus. We assessed placental transfer and exposure to infliximab (n = 3) and etanercept (n = 3) in women with autoimmune diseases. Furthermore, we perfused healthy term placentas for 6 hours with 100 µg/mL infliximab (n = 4) or etanercept (n = 5). In pregnant women, infliximab transferred into cord blood but also entered the placenta (cord‐to‐maternal ratio of 1.6 ± 0.4, placen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…FcRn also mediates transport of IgG across selective barriers such as the mucosal epithelium and the placenta (78,81,82). Transplacental transport may be particularly important to considerdue to the key developmental role of Notch signaling, Notch targeting may be harmful to the fetus.…”
Section: Specific Notch-targeting By Antibodiesmentioning
confidence: 99%
“…FcRn also mediates transport of IgG across selective barriers such as the mucosal epithelium and the placenta (78,81,82). Transplacental transport may be particularly important to considerdue to the key developmental role of Notch signaling, Notch targeting may be harmful to the fetus.…”
Section: Specific Notch-targeting By Antibodiesmentioning
confidence: 99%
“…This is in line with a previous study by Eliesen et al , which reported a low cord to maternal concentration ratio of 0.04 in a patient who used etanercept until 4 days before delivery. 7 This might be explained by the shorter half-life of etanercept (circa 3 days) compared with other TNFi (8–10 days for infliximab and 14 days for certolizumab pegol and adalimumab). Both these observations might indicate that etanercept could be used beyond GA 30–32 weeks if necessary.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 12 studies [13][14][15][16][17][18][19][20][21][22][23][24] were included, of which four studies [14,15,17,21] presented data on more than one drug. Five unique drug types were found, namely infliximab (IFX), adalimumab (ADL), vedolizumab (VDZ), ustekinumab (UST) and golimumab (GLM).…”
Section: Biologicalsmentioning
confidence: 99%
“…In conclusion, 12 studies were found that presented drug concentrations for IFX, ADL, VDZ, UST and GLM. Most studies [16,19,20,[22][23][24] only presented a concentration at delivery. The studies that presented data during the whole pregnancy showed an increase in concentration for IFX, a relative stable concentration for ADL and a decreasing concentration for VDZ.…”
Section: Interleukin 12/23 Inhibitor-ustekinumabmentioning
confidence: 99%